Endocrine disrupting and carcinogenic effects of decabromodiphenyl ether - Wang, Yi; Wang, Xinpei; Sui, Shaofeng; Liu, Zhiyan (Frontiers in Endocrinology, 2023)
Background Decabromodiphenyl ether (BDE209), an essential industrial flame retardant that is widely used, has recently been reported to be increasing in human serum. Due to the structural similarity between BDE209 and thyroid hormones, its toxic effects on the thyroid are of particular concern. Methods Original articles in the PubMed database were collected using the terms “BDE209”, “decabromodiphenyl ether”, “endocrine disrupting”, “thyroid”, “carcinogenesis”, “polybrominated diphenyl ethers”, “PBDEs,” and their synonyms from inception up to October of 2022. Results Of the 748 studies initially identified, 45 were selected, which emphasized the adverse effects of BDE209 on endocrine system. BDE209 may have a toxic effect not only on thyroid function but also on thyroid cancer tumorigenesis at multiple levels, such as by directly interfering with the TR, hypothalamic-pituitary-thyroid (HPT) axis, enzyme activity, and methylation. However, it is impossible to draw a definitive conclusion on the exact pathway of thyroid toxicity from BDE209. Conclusions Although the toxic effects of BDE209 on the thyroid have been well investigated, its tumorigenic effects remain unclear and further research is necessary.